Comparison of The Use of Type V and Type I Cement with Fly ash as Cementitious in Concrete against Chloride Ion Penetration using The Accelerated Method - Afippullah; Barnas, Edi; Soemardi, Silviati; Kusumo, Raden Sri Nugroho W.; Al Hakim, Rosyid R. (Journal of Global Engineering Research and Science, 2023)
Concrete is a composite material of several rock materials glued together by a binder. Concrete is formed from mixed aggregates (fine and coarse) and added with cement paste. This research was conducted by making concrete test objects by comparing normal type I cement concrete, concrete with added materials fly ash cement type I, and normal concrete type V in the form of a cube with a size of 15 x 15 x 15 cm for testing compressive strength and a measure of 5 x 10 cm for testing chloride ion penetration also porosity testing. This study indicates that the addition of fly ash 40% (Mix II) has a compressive strength above normal type V cement concrete (Mix III), adds resistance, and reduces the passing current and the voids in the concrete are less than normal type I cement concrete. However, it is less than normal type V cement concrete (Mix III) and is more economical than normal type V cement concrete (Mix III), normal concrete of both types of cement (Mix I and Mix II).